“Filling in all the options”: Chinese students’ choice of transnational higher education - Wu, Fanya; Liu, Ren (Journal of International Students, 2026)
This study examines the decision-making processes of students when considering transnational higher education (TNHE) programs at regional colleges and universities. Drawing on Rational Choice Theory, the study found that students tend to view TNHE as a means to access specific institutions or majors, rather than being attracted by the unique characteristics of TNHE programs. Furthermore, many students are not fully aware of the potential benefits of TNHE and express concerns about employment prospects after graduation. The study also highlights the influence of social contexts and other factors on students’ decision-making processes. Based on these findings, the study offers recommendations and suggestions for regional colleges and universities to promote TNHE programs better and support students in their decision-making.